2012
DOI: 10.1364/ome.2.001095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth pressure on erbium doped GaN infrared emitters synthesized by metal organic chemical vapor deposition

Abstract: Er doped GaN (GaN:Er) p-in structures were prepared by metal organic chemical vapor deposition. Effects of growth pressure on the optical performance of GaN:Er p-in structures have been investigated. Electroluminescence measurements revealed that the optimal growth pressure window for obtaining strong infrared emission intensity at 1.54 µm is around 20 torr, while the greater amount of Ga vacancies or non-raditive transitions were observed from the ones grown at lower or higher pressure. Our results point to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…GaN-based p-i-n structures incorporating GaN:Er in the active region have been demonstrated by Feng et al (2012). A schematic of a device structure together with IR electroluminescence spectra are shown in Fig.…”
Section: Rare-earth (Re) Doped Gallium Nitride (Gan) Emittersmentioning
confidence: 99%
“…GaN-based p-i-n structures incorporating GaN:Er in the active region have been demonstrated by Feng et al (2012). A schematic of a device structure together with IR electroluminescence spectra are shown in Fig.…”
Section: Rare-earth (Re) Doped Gallium Nitride (Gan) Emittersmentioning
confidence: 99%
“…Experimental results indicated that a FWHM < 380 arc sec is required in order to achieve GaN:Er waveguides with an optical loss less than 1 dB/cm. Previously, the attainable FWHM of GaN (0002) XRD rocking curves of GaN:Er epilayers deposited on sapphire substrate has been greater than 400 arc sec, [19][20][21] which is significantly larger than those of the typical undoped high quality GaN epilayers grown on sapphire substrate ($300 arc sec). 22 Consequently, finding effective methods to reduce the dislocation density in GaN:Er is necessary in order to realize low loss optical devices.…”
mentioning
confidence: 96%